Urethane-based electrode material for microbial fuel cells - Yugo Nishio; Dang-Trang Nguyen; Kozo Taguchi (Energy Reports, 2023)
Nowadays, global warming and fossil fuel depletion are two unsolved problems. Research is underway on renewable energies, which are new energy sources. This study aims to improve the performance of microbial fuel cells (MFCs), a renewable energy generation method. Urethane was used as the electrode material for MFC. Urethane is an excellent material suitable for use as MFC electrodes because of its durability, porosity, and other properties. However, urethane itself is not conducive. This study used conductive urethane, which is coated with activated carbon powder, as the electrode material. This material is used in deodorizing filters, air conditioning filters, and air cleaner filters. To improve the performance of MFC, carbon nanotubes and activated carbon powder were added to the urethane electrodes. PTFE was also used to improve cathodic function. PTFE is used as a binder in many microbial fuel cells. The performance of the electrodes was compared. The analysis included power density measurements and discharge characteristics. It was confirmed that the use of PTFE improves the power density by a factor of two or more. The MFC generated a maximum power density of 28.27 μW/cm2. SEM image analysis of the electrode after the experiment confirmed that PTFE could reduce the adhesion of microorganisms on the cathode surface. These results imply that the use of conductive urethanes as electrodes in MFCs is effective. The addition of carbon nanotubes, activated carbon powder, and PTFE has enabled the use of urethane as an electrode material for microbial fuel cells.